PENGARUH SOCIAL MEDIA TERHADAP PENINGKATAN BRAND AWARENESS CLOVER CLOTHING MELALUI INSTAGRAM: Studi Pada Followers Instagram Clover Clothing - Fathurroyyan, M. (2017)
Permasalahan yang terjadididalampenelitianiniadalahkurangnyabrand awareness Clover Clothing sebagaipenyediaprodukbusanamuslim. Untukmengatasimasalahtersebut, penggunaansocial mediadiharapkandapatmeningkatkanbrand awareness Clover Clothing sebagaipenyediaprodukbusanamuslim. Penelitianinibertujuanuntukmengetahuibagaimanatanggapanrespondenmengenaipenggunaansocial mediadanBrand awarenessmerek Clover Clothing, sertamengetahuiseberapabesarpengaruhpenggunaansocial mediaterhadaptingkatanBrand awarenessmerek Clover Clothing.Populasidalampenelitianiniadalahfollowersinstagram Clover Clothing yang berjumlah 2171 followers. Teknikpenentuansampel yang digunakandalampenelitianiniyaitumenggunakanteknikprobability samplingdenganmetodesimple random samplingsebanyak 100 orang.Metodeanalisis yang digunakandalampenelitianiniadalahanalisisregresi linear sederhana.Hasilpenelitianmenunjukanbahwapenggunaansocial mediatermasukdalamkategoribaikatauberpengaruh, sedangkanBrand awareness Clover Clothingtermasukdalamkategoricukupbaik.Sedangkanberdasarkanhasilpengujianhipotesismenunjukanbahwapenggunaansocial mediaberpengaruhsecarasignifikanterhadapBrand awarenessmerek Clover Clothing, Kata Kunci: Brand awarenes, Media Sosial, The problems that occur in this research is the lack of brand awareness Clover Clothing as a provider of Muslim fashion products. To overcome these problems, the use of social media is expected to increase brand awareness Clover Clothing as a provider of Muslim fashion products.This research aims to determine how the responses of respondents about the use of social media and Brand awareness of Clover Clothing and to determine how much influence of using the social media for level of Brand awareness Clover Clothing. The scope of population that used in this reaserch is Clover Clothing instagram's followers which amounted to 2171 followers. Data sampling technique using probability sampling technique with simple random sampling method, and the sample size is 100 followers. The analysis method used in this research is a simple linear regression analysis.The results showed that the use of social media in Clover Clothing is included in satisfactory category, and Brand awareness Clover Clothing included in enough category. While based on the hypothesis testing results show that the use of social media significantly positive effect on Brand awareness of Clover Clothing. Keywords: Brand Awarenes, Social Media .